2018
DOI: 10.3892/mmr.2018.8580
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic anticancer effects of ruxolitinib and calcitriol in estrogen receptor‑positive, human epidermal growth factor receptor 2‑positive breast cancer cells

Abstract: The Janus kinase (JAK)1 and JAK2 inhibitor, ruxolitinib, and the active form of vitamin D (calcitriol) were previously reported to possess anticancer effects in breast cancer. The present study investigated the combined effects of ruxolitinib and calcitriol on an estrogen receptor (ER)-positive, human epidermal growth factor receptor 2 (HER2)-positive, breast cancer cell line. The ER and HER2-positive MCF7-HER18 breast cancer cell line was used to investigate the combination effect of ruxolitinib and calcitrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…[56] These controversial results could be related to the interactions between VD 3 and the B-cell lymphoma 2 (BCL2) protein, which regulates the ER Ca 2+ release by inhibiting ITPR1 and RyR1. [57,58] Whilst VD 3 promoted Ca 2+ -dependent apoptosis in cancer cells by inhibiting BCL2, [58] the hormone promoted BCL2 during oxidative stress and inflammatory conditions, thereby preserved cell viability by constraining [Ca 2+ ] I release through ITPR1 and RyR1. [57,59] An alternative explanation for the VD 3 inhibitory effects on SOCs could also be related to the observed increase in the S100A1 protein, which alleviated myocardial infarction in animals by inhibiting [Ca 2+ ] I release through RYR1.…”
Section: Discussionmentioning
confidence: 99%
“…[56] These controversial results could be related to the interactions between VD 3 and the B-cell lymphoma 2 (BCL2) protein, which regulates the ER Ca 2+ release by inhibiting ITPR1 and RyR1. [57,58] Whilst VD 3 promoted Ca 2+ -dependent apoptosis in cancer cells by inhibiting BCL2, [58] the hormone promoted BCL2 during oxidative stress and inflammatory conditions, thereby preserved cell viability by constraining [Ca 2+ ] I release through ITPR1 and RyR1. [57,59] An alternative explanation for the VD 3 inhibitory effects on SOCs could also be related to the observed increase in the S100A1 protein, which alleviated myocardial infarction in animals by inhibiting [Ca 2+ ] I release through RYR1.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the functional role of JAK2, which can be inhibited by ruxolitinib, is not mainly involved in the growth of TAMR-MCF7 cells. Lim et al (21) recently demonstrated that ruxolitinib and calcitriol possessed synergistic anticancer effect in MCF-7 cells. Although ruxolitinib showed marginal inhibition rate in cell growth of MCF-7 cells, synergistic inhibition of cell proliferation was observed by ruxolitinib/calcitriol combination.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, ruxolitinib was shown to inhibit the proliferation of JAK2 V617F -positive Ba/F3 cells showing a constitutively active mutant form of JAK2, and to alleviate MPN symptoms in JAK2 V617F -transgenic mice (20). Moreover, involvement of JAK2 in cell proliferation was experimentally verified in various cancer cell lines, lung cancer cells (H661, H1975, H1563, ADOR, NSCLC1), breast cancer cells (MCF-7, MCF-7-HER18, SUM149, BT474, BT549, SKBR3) and glioblastoma cells (GBM6, GBM12) (21)(22)(23). However, the therapeutic effects of ruxolitinib on chemo-resistant breast cancer cells, and especially TAM-resistant cells, remain obscure.…”
Section: Inhibition Of Tumor Growth and Angiogenesis Of Tamoxifen-resmentioning
confidence: 97%
See 1 more Smart Citation
“…The JAK1/2-selective inhibitor ruxolitinib is FDA approved for the treatment of polycythemia vera, myelofibrosis, and graft versus host disease, and it has been shown to decrease STAT3 activation in preclinical models of several solid tumors [18,22,65] . Ruxolitinib inhibited STAT3 activation and decreased cell growth in breast cancer [66,67] , NSCLC [68] , HNC [69] , esophageal cancer [70] , bladder cancer [71] , HCC [72] , cervical cancer [73] , and colorectal cancer [74,75] cell lines. In pancreatic cancer cells, ruxolitinib treatment was also shown to decrease expression of pro-angiogenic genes and impede epithelial-to-mesenchymal transition [76,77] .…”
Section: Ruxolitinibmentioning
confidence: 99%